2021
DOI: 10.3389/fbioe.2021.780993
|View full text |Cite
|
Sign up to set email alerts
|

Thiadiazoloquinoxaline-Based Semiconducting Polymer Nanoparticles for NIR-II Fluorescence Imaging-Guided Photothermal Therapy

Abstract: Phototheranostics have gained more and more attention in the field of cancer diagnosis and therapy. Among a variety of fluorophores for phototheranostics, semiconducting polymer nanoparticles (SPNs), which are usually constructed by encapsulating hydrophobic semiconducting polymers (SPs) with amphiphilic copolymers, have shown great promise. As second near-infrared (NIR-II) fluorescence imaging has both higher imaging resolution and deeper tissue penetration compared with first near-infrared (NIR-I) fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…FL imaging in the second NIR window (NIR-II, 1000–1700 nm) has attracted increasing interest due to its advantages for in vivo imaging. Compared with light in the visible region and the first NIR window (NIR-I, 650–950 nm), NIR-II FL imaging possesses significantly enhanced temporal-spatial resolution, deeper tissue penetration, and lower scattering losses. For example, Zhang et al reported on the dynamic monitoring of pH changes in vivo based on dual-channel ratiometric NIR-II FL imaging using a series of pH transition point (pHt) tunable sensors (pTAS) . In the pTAS sensor, NIR-II-emissive aza-BODIPY (NAB) acted as an energy donor and provided a self-calibrated reference signal.…”
Section: Ratiometric Optical Imagingmentioning
confidence: 99%
“…FL imaging in the second NIR window (NIR-II, 1000–1700 nm) has attracted increasing interest due to its advantages for in vivo imaging. Compared with light in the visible region and the first NIR window (NIR-I, 650–950 nm), NIR-II FL imaging possesses significantly enhanced temporal-spatial resolution, deeper tissue penetration, and lower scattering losses. For example, Zhang et al reported on the dynamic monitoring of pH changes in vivo based on dual-channel ratiometric NIR-II FL imaging using a series of pH transition point (pHt) tunable sensors (pTAS) . In the pTAS sensor, NIR-II-emissive aza-BODIPY (NAB) acted as an energy donor and provided a self-calibrated reference signal.…”
Section: Ratiometric Optical Imagingmentioning
confidence: 99%
“…Typical electron acceptors for organic semiconductor nanomaterials in NIR-II regions include benzobisthiadiazole (BBT), thiadiazoloquinoxaline (ATQ), and thiadiazolobenzotriazole (TBZ). 164 These electron acceptors can be polymerized with proper electron donor units, forming donor–acceptor (D–A) or donor–acceptor–donor (D–A–D) conjugates (Fig. 4C).…”
Section: Structure Of Nanocatalysts For Immunomodulationmentioning
confidence: 99%
“…Exogenous contrast agents, chemical dyes, and all kinds of nanostructures (carbon nanomaterials, gold nanomaterials, transition metal dichalcogenides, etc) are extensively studied recently. [49][50][51] As shown in Table 4, nanoparticles, contrast agents, and nanocrystals have high occurrence and total link strength.…”
Section: Research Hotspots and Emerging Topicsmentioning
confidence: 99%